2020
DOI: 10.1186/s12871-020-00964-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of anesthetic depth and EEG band power using phase lag entropy during propofol anesthesia

Abstract: Background: Phase lag entropy (PLE) is a novel anesthetic depth indicator that uses four-channel electroencephalography (EEG) to measure the temporal pattern diversity in the phase relationship of frequency signals in the brain. The purpose of the study was to evaluate the anesthetic depth monitoring using PLE and to evaluate the correlation between PLE and bispectral index (BIS) values during propofol anesthesia.Methods: In thirty-five adult patients undergoing elective surgery, anesthesia was induced with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Therefore, theoretically, the PLE score could be less affected by EEG than the BIS; however, there have been few studies on the relationship between the PLE score and PLE-EMG. Although several studies showed PLE score has correlation with BIS for evaluating consciousness and depth of anesthesia during general anesthesia (11,12,24), the present study is meaningful since it is the first to investigate the PLE-EMG effect on the PLE score.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, theoretically, the PLE score could be less affected by EEG than the BIS; however, there have been few studies on the relationship between the PLE score and PLE-EMG. Although several studies showed PLE score has correlation with BIS for evaluating consciousness and depth of anesthesia during general anesthesia (11,12,24), the present study is meaningful since it is the first to investigate the PLE-EMG effect on the PLE score.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study reported no changes in the BIS score even after 10 min of sugammadex reversal (22); however, the EMG activity was a single entity rather than dividing it into low and high groups, which may differ from other studies. The PLE monitor has been recently approved for clinical use, with several studies assessing its usefulness and comparison with the BIS; moreover, it has been shown as useful for LOC evaluation in general anesthesia (11,12,23,24). PLE employs EEG signals with ranges of 0.1-1 and 32-45 Hz while PLE-EMG uses signals >45 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…This algorithm is similar to PLE (phase lag entropy) that uses four-channel EEG to measure the temporal pattern diversity in the phase relationship of frequency brain signals [ 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Electroencephalography (EEG) is a biosignal that is widely used in research and clinical practices, including pain quantification, 1 brain-computer interface applications (e.g. wheelchair control), 2,3 sleep studies, 4 anesthetic depth monitoring, 5 and diagnosis of conditions (e.g., epilepsy, head injuries, dizziness, brain tumors, psychiatric conditions). [5][6][7] This signal starts at a frequency of 0.1 to 0.7 Hz and ends at 30 to 100 Hz.…”
mentioning
confidence: 99%
“…wheelchair control), 2,3 sleep studies, 4 anesthetic depth monitoring, 5 and diagnosis of conditions (e.g., epilepsy, head injuries, dizziness, brain tumors, psychiatric conditions). [5][6][7] This signal starts at a frequency of 0.1 to 0.7 Hz and ends at 30 to 100 Hz. It has an amplitude range from 10 to 100 µV.…”
mentioning
confidence: 99%